Role of Notch signaling in regulating innate immunity and inflammation in health and disease. Issue 3 (2nd March 2016) - Shang, Yingli; Smith, Sinead; Hu, Xiaoyu
Abstract: The Notch signaling pathway is conserved from Drosophila to mammals and is critically involved in developmental processes. In the immune system, it has been established that Notch signaling regulates multiple steps of T and B cell development in both central and peripheral lymphoid organs. Relative to the well documented role of Notch signaling in lymphocyte development, less is known about its role in regulating myeloid lineage development and function, especially in the context of acute and chronic inflammation. In this review article, we will describe the evidence accumulated during the recent years to support a key regulatory role of the Notch pathway in innate immune and inflammatory responses and discuss the potential implications of such regulation for pathogenesis and therapy of inflammatory disorders.